Carboxymethylation of the polysaccharide from the fermentation broth of Marasmius androsaceus and its antidepressant mechanisms - Yu Qiu; Yan Su; Jia Song; Fangming Mou; Jia Gou; Xiaoqi Geng; Xinyue Li; Zhiqiang Nie; Jianxin Wang; Yu Zheng; Min Wang (Food Science and Human Wellness)
To investigate the structure-activity relationship of polysaccharide and obtain a better antidepressant polysaccharide, the antidepressant-like activity of a carboxymethyl polysaccharide (C-MEPS2) subjected to submerged fermentation was systematically studied. PC12-H cell and Kunming mice were used to investigate the differences and their mechanism in the antidepressant effects of C-MEPS2 and MEPS2. Cell experiments have showed that C-MEPS2 has a better antidepressant effect than MEPS2. C-MEPS2 could exert antidepressant effects related to catecholamine synthesis with specific sites of TH, D2DR, and P-CAMKII. In addition, C-MEPS2 could repair the Res-induced damage in PC12-H cell, stabilize the mitochondrial membrane potential and regulate intracellular Ca2+ concentration, thus reducing cell apoptosis caused by RES. Antagonists common dosing experiments on animals further proved that CMEPS2 could significantly improve the antidepressant effect of derivatives without affecting the antidepressant mechanism of MEPS2. It is speculated that it may be related to carboxymethylated modification.